2012
DOI: 10.1103/physrevd.86.124006
|View full text |Cite
|
Sign up to set email alerts
|

BRST analysis of physical fields and states for 4D quantum gravity onR×S3

Abstract: We consider the background-free quantum gravity based on conformal gravity with the Riegert-Wess-Zumino action, which is formulated in terms of a conformal field theory. Employing the R×S 3 background in practice, we construct the nilpotent BRST operator imposing diffeomorphism invariance. Physical fields and states are analyzed, which are given only by real primary scalars with a definite conformal weight. With attention to the presence of background charges, various significant properties, such as the state-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 39 publications
(118 reference statements)
4
16
0
Order By: Relevance
“…This anomalous dimension vanishes at b → ∞, which is consistent with the classical limit of gravity. Here, note that the α t -independent terms inγ EH (2.14) andγ Λ (2.15) agree with the exact solutions of these anomalous dimensions derived using BRST conformal symmetry at α t = 0 [22,24,26,27].…”
Section: Renormalizations Of Mass Parameterssupporting
confidence: 65%
See 1 more Smart Citation
“…This anomalous dimension vanishes at b → ∞, which is consistent with the classical limit of gravity. Here, note that the α t -independent terms inγ EH (2.14) andγ Λ (2.15) agree with the exact solutions of these anomalous dimensions derived using BRST conformal symmetry at α t = 0 [22,24,26,27].…”
Section: Renormalizations Of Mass Parameterssupporting
confidence: 65%
“…1 To further resolve the ghost problem, we constructed renormalizable quantum conformal gravity several years ago [10,11,12] by applying a nonperturbative method learned from the development of two-dimensional quantum gravity [13,14,15,16,17,18]. The conformal factor of the metric field is treated exactly without introducing a coupling constant for it [19,20,21,22,23,24,25], and as a result the theory has Becchi-Rouet-StoraTyutin (BRST) conformal symmetry in the UV limit, which represents the background-free property of quantum gravity as a gauge equivalency under conformal transformations [26,27]. This symmetry makes ghost modes unphysical exactly.…”
Section: Introductionmentioning
confidence: 99%
“…is the charge for the cosmological constant operator defined by d 4 x : e γφ : [5,9,10,11]. In this way, we have seen that the renormalization manner proposed here can reproduce the exact anomalous dimension.…”
Section: Cosmological Constant Operatormentioning
confidence: 56%
“…It has been known that the Riegert action plays a significant role to realize it [4,5,6,7,8]. We then have shown that the Riegert theory including the kinetic term of the Weyl action has such a gauge symmetry as a part of diffeomorphism invariance, which is so strong that physical fields are restricted to "real composite scalars" (called primary scalars) only [9,10,11]. 2 The model we consider here is the renormalizable quantum theory of gravity expanded just from this background-free system by a single dimensionless coupling constant that brings the dynamics of traceless tensor fields.…”
Section: Introductionmentioning
confidence: 96%
“…In this way, we can realize the background-free nature of quantum gravity. The BRST conformal algebra has been constructed, and by solving the BRST invariance condition, it has been shown that physical states are given by real primary scalar fields only [17,18], 1 which is consistent with scalar-dominated spectra of the early universe. 1 Due to the presence of this symmetry, ghost modes are no longer gauge invariant.…”
Section: Introductionmentioning
confidence: 99%